ASURANSI SEBAGAI LEMBAGA EKONOMI DALAM PERSPEKTIF HUKUM ISLAM - Jaman, Najmah; Ma’ruf, Amar; Ma’arif, Fikrul (Indonesian Journal of Shariah and Justice, 2022)
Muslims today are faced with contemporary economic problems caused by the development of science and technology. For this reason, Islamic economics must be able to face or answer and provide solutions or alternatives to growing economic problems, one of which is the problem of insurance. Insurance, which is closely related to muamalat, is a new type of contract that has generated a lot of discussion and opinion about insurance law from an Islamic point of view. Therefore insurance needs to be studied in depth in the perspective of Islamic law, both conventional insurance and sharia insurance.